EPISTEMOLOGICAL OBSTACLES SISWA DALAM MEMAHAMI GEOMETRI DASAR SUDUT SALING BERPENYIKU DI KELAS VII SMP - Khomeni, Ayathollah (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
Geometry learning can train students in analyzing the characteristics of geometric shapes and making mathematical arguments regarding visualization, spatial reasoning and geometric modeling in problem solving. Several studies show that students experience difficulties and make mistakes in solving geometry problems. The errors and difficulties experienced by students indicate the occurrence of epistemological learning barriers. This research aims to analyze the epistemological type of learning obstacle in learning angles in basic geometry material in junior high school. This research method is a qualitative type with a Didactical Design Research model approach through retrospective analysis. This research states that students experience epistemological learning obstacles in the three types of epistemological concept, epistemological procedure and epistemological operational technique.